Logolicious! : a tasty collection of the best logos from around the globe - Top, Peleg, 1967- (Collins Design, 2010)
A snapshot of today's most visually delicious logos, selected by some of the world's top designers. From iconic symbols to dramatic wordmarks, Logolicious features more than 1,000 inspirational examples of modern logo work. More than a professional guidebook, it is a visually compelling look at the movers and shakers shaping today's design culture